Multiple concurrent partnerships and sexual dissatisfaction - an exploratory study among black women in South Africa. - Rassool, Rayana (My University, 2011)
This research report focuses on the linkages between multiple concurrent partnerships and sexual dissatisfaction in a sample of black women. Multiple Concurrent Partnerships has been identified as a key driver of HIV/AIDS in Southern Africa and it has been posited that one of the factors contributing to MCP is women’s sexual dissatisfaction; the focus of this research. The research was firmly entrenched in a social constructionist paradigm strongly rejecting a biomedical approach to understanding sexuality. The research was located in a qualitative framework. Data was collected though focus groups and in depth interviews with young women aged 18 – 35 in an urban township in Johannesburg. A sexually satisfying relationship is an important component of women’s lives. Where main partners did not provide sexual satisfaction, many women sought pleasure elsewhere. However sexual dissatisfaction is also interwoven with other complex social issues such as gender based violence, transactional sex and poverty. This study calls for greater attention to be paid to the ways in which women want to maximise their sexual enjoyment and minimise sexual harm.